A double blind, randomised, placebo-controlled trial to evaluate the efficacy of metformin to treat preterm pre-eclampsia (PI2 Trial): study protocol. Issue 4 (24th April 2019) - Cluver, Catherine; Walker, Susan P; Mol, Ben W; Hall, David; Hiscock, Richard; Brownfoot, Fiona C; Kaitu'u-Lino, Tu'uhevaha J; Tong, Stephen
Abstract : Introduction: Pre-eclampsia is a major complication of pregnancy, globally responsible for 60 000 maternal deaths per year, and far more fetal losses. There is no definitive treatment other than delivery. A therapeutic that could quench the disease process would be useful to treat preterm pre-eclampsia, as it could allow these pregnancies to safely continue to a gestation where fetal outcomes are significantly improved. We have published preclinical data to show that metformin, a drug known to be safe in pregnancy and commonly used to treat gestational diabetes, has potent biological effects making it another promising candidate to treat pre-eclampsia. Here, we describe a phase II clinical trial to examine whether administering extended-release metformin may be effective in treating women with preterm pre-eclampsia (PI2 Trial). Methods: The PI2 Trial is a phase II, double blind, randomised controlled trial that aims to recruit 150 women with preterm pre-eclampsia (gestational age 26+0 to 31+6 weeks) who are being managed expectantly. Participants will be randomised to receive either 3 g of metformin or placebo daily. The primary outcome is time from randomisation until delivery. A delay in delivery of 5 days is assumed to be clinically relevant. The secondary outcomes will be a maternal composite and neonatal composite outcome. All other outcomes will be exploratory. We will record adverse events. Ethics and dissemination: This study has ethical approval (Protocol number M16/09/037 Federal Wide Assurance Number 00001372, Institutional Review Board Number IRB0005239), is registered with the Pan African Clinical Trial Registry (PACTR201608001752102) and the South African Medicine Control Council (20170322). Data will be presented at international conferences and published in peer-reviewed journals. Trial registration number: PACTR201608001752102; Pre-results.